2021
DOI: 10.1186/s40729-021-00304-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of implant protrusion length on non-grafting osteotome sinus floor elevation with simultaneous implant: a 3- to 9-year retrospective study

Abstract: Background This study analyzed the influence of implant protrusion length (IPL) on the possible factors that affect the long-term outcomes utilizing non-grafting osteotome sinus floor elevation (OSFE) with simultaneous implant placement, and to explore the optimal range of IPL. Materials and methods A retrospective study design was adopted. The clinical and radiographic data of 105 implants in 65 patients were collected after 3–9 (mean 5.04) years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…tween the LC group and the RC group. The correlation between implant protrusion length and bone formation and the correlation between residual bone conditions and marginal bone loss were both illustrated in previous studies(Galindo-Moreno et al, 2015;Klijn et al, 2012;Park et al, 2019;Yu et al, 2021). Therefore, we measured these parameters during the immediate postoperative period.…”
mentioning
confidence: 62%
“…tween the LC group and the RC group. The correlation between implant protrusion length and bone formation and the correlation between residual bone conditions and marginal bone loss were both illustrated in previous studies(Galindo-Moreno et al, 2015;Klijn et al, 2012;Park et al, 2019;Yu et al, 2021). Therefore, we measured these parameters during the immediate postoperative period.…”
mentioning
confidence: 62%
“…ESBG is a repeated measured variable (Table S4), the baseline was immediately after surgery (T1), and the follow‐up time point was pre‐prosthetic restoration (T2). Of the 23 confounding variables (Yu et al, 2021), five variables had poor standardized difference scores. After PSM, there were 51 patients with 61 implants in the RBH ≤ 4 mm group and 73 patients with 112 implants in the RBH > 4 mm group, which declined from a median of 5.97 to 5.05 mm, from a median 3.40 to 2.69 mm, respectively (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…19,[28][29][30] However, the increased implant protrusion length seems not to be proportional to the amount of ESBG. 12,13 A previous study revealed a decrease in ESBG when the implant protrusion length exceeded 4 mm. 12 Moreover, an increased implant protrusion length in conjunction with OMSFE without a grafting material creates a larger cavity underneath the elevated membrane, which causes a greater pressure on the membrane during the early healing period, with the risk of the coagulum dissolving and compromised bone regeneration.…”
Section: Discussionmentioning
confidence: 96%
“…12,13 A previous study revealed a decrease in ESBG when the implant protrusion length exceeded 4 mm. 12 Moreover, an increased implant protrusion length in conjunction with OMSFE without a grafting material creates a larger cavity underneath the elevated membrane, which causes a greater pressure on the membrane during the early healing period, with the risk of the coagulum dissolving and compromised bone regeneration. 13 Consequently, it is recommended that the exposed implant surface within the maxillary sinus does not exceed 5 mm following OMSFE with or without a grafting material.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation